2020
DOI: 10.1136/archdischild-2020-319103
|View full text |Cite
|
Sign up to set email alerts
|

Children and young people’s concerns and needs relating to their use of health technology to self-manage long-term conditions: a scoping review

Abstract: BackgroundThe use of patient-facing health technologies to manage long-term conditions is increasing; however, children and young people may have particular concerns or needs before deciding to use different health technologies.AimsTo identify children and young people’s reported concerns or needs in relation to using health technologies to self-manage long-term conditions.MethodsA scoping review was conducted. We searched MEDLINE, PsycINFO and CINAHL in February 2019. Searches were limited to papers published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 79 publications
(73 reference statements)
0
21
0
Order By: Relevance
“…Participants' evaluations of the MMI were mostly positive. It was notable that no concerns were expressed about privacy and confidentiality associated with the online information, as these concerns have been prominent in other research (Blower et al, 2020). However, this was a hypothetical study setting for these participants and the MMI did not require users to input personal information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants' evaluations of the MMI were mostly positive. It was notable that no concerns were expressed about privacy and confidentiality associated with the online information, as these concerns have been prominent in other research (Blower et al, 2020). However, this was a hypothetical study setting for these participants and the MMI did not require users to input personal information.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, access to digital information and technology is not universal, and unequal access may compound existing income-related health inequalities ( Office for National Statistics, 2019 ). In addition, a recent systematic scoping review highlighted important concerns that children and adolescents have about digital health technologies, including privacy and trustworthiness ( Blower et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, children and their families may have privacy, security and trust concerns regarding digital tools. 4 . There is a need to help patients and families navigate these technologies, understand issues of safety and effectiveness as well as trust and data security, and support their use for maximum benefit.…”
Section: The New Age: a Digital Revolution Is Underwaymentioning
confidence: 99%
“…2 Involving CYP with diabetes in developing and using health technologies provides opportunities for enhancing their health and well-being. 3 Provider bias has been reported to be an important systemic factor that may play a role in barriers to access. One study reported that providers were significantly less likely to recommend more than four blood glucose checks day to African-American families compared to non-Hispanic Caucasian families.…”
Section: Introductionmentioning
confidence: 99%